The Causality between Economic Growth, Public Debt and Government Spending of Lao PDR - PHIMMASAEN, Bouasy; CHANTHAVONE, Thongphanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper aims to test the causality between economic growth, public debt and government spending. This study used the time series data from 1995-2021 and implied with a VAR model and Granger causality test. In addition, the unit root, cointegration, Lagrange multiplier and Jarque-Bera test statistics was used. The empirical analysis by using VAR model found that public debt and economic growth have no effect on public spending. But government spending affects public debt in the same direction with a statistical significance level of 0.1 meaning that only government spending affects public debt, while public debt does not affect government spending. While government spending and public debt affect economic growth in the same direction with a statistical significance level of 0.01. For the Granger Causality Test, there is a unidirectional relationship means that only government spending and public debt affect economic growth, economic growth does not affect government spending and public debt.